(untitled) (AYUSHDHARA, 2024)
Marma Chikitsa is a gem of Ayurveda, a non-invasive therapy in which a very gentle stimulation of Marma points is done to instigate the flow of Prana which was occluded due to disturbed flow of Vata. To perform this therapy, a particular amount of pressure is to be applied on the specific Marma point. This study is being conducted to assess the pressure pain threshold of value of Marma in healthy individuals. Pressure pain threshold, was measured accordingly by a device called “Pressure Algometer” on Rujakara Marma i.e., Manibandha, Kurchashira and Gulpha for left as well as right side. The pressure was applied by algometer at two sites that is, at the centre point of Marma and other on the periphery of the Marma, within the range of Pramana of Marma (according to the Pramana, as described in the text). Time duration for the procedure on a particular Marma will be from the skin surface contact with algometer till Grade 2 of pain scale (VAS) and the reading of algometer will be recorded for each Rujakara Marma in a particular volunteer. The results are recorded and shared in this article.